Response Time Analysis of Websites Using Jmeter Tool - Goyal, Shaily; Kaushik, Manju (International Journal of Computer Sciences and Engineering, 2025)
Academic institutions use websites for several purposes like examination enrollment, form submission, result declaration and more. However, while accessing those websites applicants encounter several issues like server errors or response timeout failures. Several factors are responsible for such technical issues like heavy traffic, infrastructure limitations etc. The aim of this research paper is to evaluate the response time of different academic websites (both public and private) with the help of jmeter tool. The findings of this research indicate the critical factors behind delayed response time. The paper discusses these results and on their basis, provides certain insights for achieving better response time.